PELAKSANAAN PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU DALAM PENDISTRIBUSIAN GAS LPG 3 KG DI KOTA PEKANBARU - Bayu Anggara; Syapril Abdullah (UIR Press, 2017)
This research was conducted at the Department of Industry and Trade City Pekanbaru which supervises the distribution of LPG gas 3 Kg, and pengawai Who works at the Department of Industry and Trade Pekanbaru City and LPG gas distributor 3 Kg located in Pekanbaru Town, Marpoyan Damai Sub-district The purpose of this study is to analyze the implementation of supervision of the Office of Industry and Trade Pekanbaru City in the distribution of LPG gas 3 Kg in Pekanbaru City and the inhibiting factors in carrying out supervision of gas distribution LPg 3 Kg in Pekanbaru City. Determination of the number of samples for employees of Pekanbaru City Trade and Distribution Service using sample sensu so that it can be 4 employees, while samples from LPG gas distributor 3 Kg by assigning 30 dealers from 58 dealers by using randl sampling technique. The type of data used in this study includes primary data and secondary data. Data collection techniques used were observation, questionnaires and interviews. Data analysis technique used by the writer is descriptive qualitative that is in the form of tables and depiction through interview result in field by looking at respondent's answer to the implementation of supervision of Industry and Trade Office Pekanbaru City in Distribution 3 Kg LPG gas in Pekanbaru City, The steps taken in improving the implementation of the supervision of the distribution of LPG gas 3 Kg in the form of data that has been collected are analyzed by describing the existing problems and providing interpension to the relevant results then drawn conclusions. From the research can be concluded that the results obtained are still not according to the rules alias not optimal. Where the inhibiting factors for the supervision of LPG gas distribution are 3 Kg, namely, limited human resources, lack of awareness from the LPG 3 LPG bases on the distribution of 3 kg LPG gas, and the village / kelakarta apparatus and the rt and rw levels which Still do not understand the duties and functions of their positions in the participation of this 3 Kg LPG gas circulation.